1994
DOI: 10.1007/bf00173022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the centrally acting cholinesterase inhibitors tetrahydroaminoacridine and E2020 on the basal concentration of extracellular acetylcholine in the hippocampus of freely moving rats

Abstract: The effects of the centrally acting cholinesterase (ChE) inhibitors, tetrahydroaminoacridine (THA) and E2020 (1-benzyl-4-[(5,6-dimethoxy-1-indanon)-2-yl] methylpiperidine hydrochloride), potential drugs for the treatment of senile dementia, on the basal extracellular acetylcholine (ACh) concentration in the hippocampus of freely moving rats, were determined using a microdialysis technique without the use of a ChE inhibitor in the perfusion fluid and a sensitive RIA. The mean (+/- SEM) basal ACh content in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…This mechanism of action has been experimentally confirmed in rats (Kawashima et al, 1994;Kosasa et al, 1999) and monkeys (Tsukada et al, 2004), as measured qualitatively by microdialysis. Since [ 11 C]MP4A is a substrate-type radiotracer, the increase in synaptic acetylcholine levels would affect k 3 of [ 11 C]MP4A through two mechanisms as follows.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This mechanism of action has been experimentally confirmed in rats (Kawashima et al, 1994;Kosasa et al, 1999) and monkeys (Tsukada et al, 2004), as measured qualitatively by microdialysis. Since [ 11 C]MP4A is a substrate-type radiotracer, the increase in synaptic acetylcholine levels would affect k 3 of [ 11 C]MP4A through two mechanisms as follows.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, using microdialysis, it is reported that donepezil dose-dependently increases the extracellular acetylcholine concentration in rats (Kawashima et al, 1994;Kosasa et al, 1999) and in monkey (Tsukada et al, 2004), which may cause additional AChE inhibition (substrate inhibition) (Reiner and Radic, 2000). With positron emission tomography (PET), not only can we assess brain AChE inhibition by a reversible inhibitor without tissue-dilution effect, but also we can evaluate the inhibitory effects of increased synaptic acetylcholine levels on AChE in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that AChE inhibitors such as physostigmine act by increasing synaptic ACh (Kawashima et al, 1994;Scali et al, 1997), resulting in competition with scopolamine at the postsynaptic muscarinic receptors. In agreement with this view, tacrine and donepezil attenuated or completely blocked the inhibitory effects of scopolamine depending on the dose of the muscarinic receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…After donepezil, 0.5 and 2.0 mg/kg s.c. the ACh levels were at 30 min twice and at 1 h 21 times the control value (24). After donepezil at 0.65 and 2 mg/kg i.p., the increase was 4 and 12 times, respectively, the peak effect occurred within 1 h (37). In this respect donepezil was more potent than tacrine (37).…”
Section: Pharmacologymentioning
confidence: 78%
“…Donepezil increased extracellular ACh levels in the hippocampus and cortex of rats (24,37). After donepezil, 0.5 and 2.0 mg/kg s.c. the ACh levels were at 30 min twice and at 1 h 21 times the control value (24).…”
Section: Pharmacologymentioning
confidence: 92%